FAMILY WITH AN ELDERLY AND DEPENDENT PERSON IN THE FACE OF SOCIO-DEMOGRAPHIC CHANGES IN POLAND - Bojanowska, Elżbieta (Uniwersyteckie Czasopismo Socjologiczne, 2016)
Changes in the family structure, arising from the transformations of matrimonial and reproductive behaviours, including a decrease in the number of births below simple replacement of generations, the prolongation of the average lifespan and migrations are intensifying the aging process of the Polish society. Therefore, one of more important contemporary problems is the growth of the share of people in the population who will require the support in the basic everyday activities and will not be able to function independently without the assistance of third parties, both in the domestic and social environment. The consequence is the necessity to build a decentralised and comprehensive (coherent) system of caring for elderly and dependent people. When shaping the system of care and assistance, first of all a possibility to choose the form of care and assistance by an elderly and dependent person should be considered, compliant both with personal preferences, as well as with financial abilities. Secondly, in accordance with subsidiarity, close cooperation of local governments in the provision of services with the closest surrounding of an elderly person should be provided. Moreover, proper conditions for meeting the needs of the elderly should be created, also through the support for families and their closest environment, among others via the extension of the catalogue of services in the place of residence, directed at informal elderly caregivers.